Characterization of the equine skeletal muscle transcriptome identifies novel functional responses to exercise training - McGivney, Beatrice A; McGettigan, Paul A; Browne, John A; Evans, Alexander CO; Fonseca, Rita G; Loftus, Brendan J; Lohan, Amanda; MacHugh, David E; Murphy, Barbara A; Katz, Lisa M; Hill, Emmeline W (BMC genomics, 2010)
Background Digital gene expression profiling was used to characterize the assembly of genes expressed in equine skeletal muscle and to identify the subset of genes that were differentially expressed following a ten-month period of exercise training. The study cohort comprised seven Thoroughbred racehorses from a single training yard. Skeletal muscle biopsies were collected at rest from the gluteus medius at two time points: T 1 - untrained, (9 ± 0.5 months old) and T 2 - trained (20 ± 0.7 months old). Results The most abundant mRNA transcripts in the muscle transcriptome were those involved in muscle contraction, aerobic respiration and mitochondrial function. A previously unreported over-representation of genes related to RNA processing, the stress response and proteolysis was observed. Following training 92 tags were differentially expressed of which 74 were annotated. Sixteen genes showed increased expression, including the mitochondrial genes ACADVL , MRPS21 and SLC25A29 encoded by the nuclear genome. Among the 58 genes with decreased expression, MSTN , a negative regulator of muscle growth, had the greatest decrease. Functional analysis of all expressed genes using FatiScan revealed an asymmetric distribution of 482 Gene Ontology (GO) groups and 18 KEGG pathways. Functional groups displaying highly significant ( P < 0.0001) increased expression included mitochondrion, oxidative phosphorylation and fatty acid metabolism while functional groups with decreased expression were mainly associated with structural genes and included the sarcoplasm, laminin complex and cytoskeleton. Conclusion Exercise training in Thoroughbred racehorses results in coordinate changes in the gene expression of functional groups of genes related to metabolism, oxidative phosphorylation and muscle structure.